THE CRISIS OF ECOLOGICAL MEANING IN TRADITIONAL RITUALS UNDER TOURISM REGIME IN POST-REFORMATION INDONESIA - Ikwan Setiawan; Albert Tallapessy; Andang Subaharianto (Proceeding of International Conference on Art, Language, and Culture, 2017)
This paper aims to discuss the crisis of ecological significance that occurred in traditional rituals in the post-Reform era. Traditional rituals that genealogically seek to integrate human relationships with supernatural powers and natural harmony are massively incorporated into the tourism mechanism. To discuss the issue, we will combine Foucauldian and post-colonial exotic perspectives. The research data we took from our field research in Banyuwangi and news in online media. We analyze the data to find the hegemonic inclination in interpreting ritual under tourism regime. The results of this study indicate that the post-Reformation state regime increased ritual-based tourism activity to gain maximum financial benefits. Gradually, people are also affected by the hegemony of the discourse, so they begin to regularly celebrate rituals without emphasizing the ecological power in them. Under these conditions an eco-cultural movement is needed that can raise public awareness of the importance of returning to integrating rituals with ecological problems.